Economics of insurance - Borch, Karl H. (Karl Henrik), 1919-1986 (Advanced textbooks in economics, 1990)
The theory of insurance is presented in this book, discussed from the viewpoint of the theory of economics of uncertainty. The principle of premium calculation which the book uses is based on economic equilibrium theory and differs from many of the premium systems discussed by actuaries.